Consumer’s attitude of halal certified product / Norhidayu Hut - Hut, Norhidayu (2016)
The title of this study is “To Determine Consumer Attitude of Halal Certified Product”. The chosen study was located in Negeri Sembilan which is a micro industries organization. The purpose of this study is to determine consumer attitude of halal certified product among customer Warisan Nismilan Food.The researcher distributed 100 questionnaires to complete this study and used Statistical Package for the Social Science (SPSS) version 23.0 to carry out new findings in the consumer attitude of Halal certified product which is promotion, attractive and quality, Halal certification and price. The results of this study have been proven the consumer’s attitude towards Halal certified product. Therefore this issue must be to determining by the organization to improve company performance and increase company profitability.